Autoantibodies to NR2A Peptide of the Glutamate/NMDA Receptor in Patients with Seizure Disorders in Neuropsychiatric Systemic Lupus Erythematosus - Yang, Yan; Yuan, Chao; Shen, Shu-qun; Wang, Xue-er; Mei, Qing-hua; Jiang, Wen-qing; Huang, Qin (Mediators of Inflammation, 2017)
Objective. Seizure disorders are one of the most disabling, life-threatening, and the least understood syndromes associated with neuropsychiatric SLE (NPSLE). N-Methyl-D-aspartate (NMDA) receptors are a subgroup of the glutamate receptor family, whose NR2A subunit was found on neuronal cells (anti-NR2A) in NPSLE patients with different types of epilepsy. The present study was conducted to determine the serum levels of anti-NR2A antibodies in a large group of SLE patients, to investigate the possible correlation between the presence of the NR2A specific antibodies and NPSLE-related seizure disorders. Methods and Results. The study population consisted of 107 SLE patients and 43 age- and sex-matched healthy controls. 73 SLE patients had active disease. 36 of these had NPSLE. NMDA levels were measured by ELISA. Clinical and serological parameters were assessed according to routine procedures. The levels of anti-NR2A antibodies were significantly higher in NPSLE patients, compared with non-NPSLE patients and healthy controls. Furthermore, the levels of NPSLE in patients with seizure disorders were shown to be higher than in those with cognitive dysfunction and other CNS symptoms, however, without significance. Increase in serum anti-NR2A antibodies levels correlated to anti-dsDNA antibody and SLEDAI as well as complement levels. Conclusion. We suggest that anti-NR2A antibodies play a role in the pathogenesis of NPSLE with seizure disorders.